Synthesis, Characterization and Anticancer Study of New3-[(2Z)-2(2-hydroxybenzylidene) hydrazinyl]-5-(2-hydroxyphenyl)-1, 3, 4-oxadiazol-3-ium and its Transition Metal Complexes - Al alawy, Hadeel; Ibrahim A. Flifel (University of Thi-Qar Journal of Science, 2023)
A new ligand 2-{5-[2-(2-hydroxybenzylidene)hydrazinyl]-1,3,4-oxadiazol-2-yl}phenol (L)  was prepared  and  characterized  by Infrared Spectra, H1 Nuclear magnatic resonance, C13 Nuclear magnatic resonance , and mass spectroscopy.  ligand was used as  chelating ligand  to prepare some  of  transition metal complexes with Ni(II), Co(II), and Cr(III). The prepared complexes  were  characterized  by FTIR, mass spectroscopy and conductance measurement. The hyper chem. program 7.51 was used for theoretical study using PM3 methodor the purpose of this study,. Regarding the information obtained about the complexes, we can suggest the octahedral geometry for Cr (III) complex, tetrahedral geometry for Co(II) and square planer for Ni(II). The effectiveness of these ligands against the breast cancer  was studied and  showed excellent results. the most active derivatives of 1,3,4-oxadiazole exceeded the effect of reference drugs, so they may become the main new anti-cancer drugs in the future.